A atração pelo desconhecido e a visão da América na obra de Marie van Langendonck - Fachinelli, Pamela Pinto Chiareli; Araújo, Joana Luiza Muylaert de; Tabak, Fani Miranda (Letras de Hoje, 2015)
O livro Uma Colônia no Brasil que é pouco conhecido no meio acadêmico. Escrito por uma belga, Madame van Langendonck, relata as experiências da autora em terras brasileiras no período em que residiu em uma colônia ao sul do país, entre os anos de 1857 e 1859. Marie van Langendonck, aos sessenta anos, embarcou em um navio de emigrantes seduzida pelo desejo de vivenciar a floresta virgem do Brasil. Acredita-se que a viajante tenha absorvido a visão edênica de um mundo virgem revivida no Romantismo. Assim, busca-se discutir a construção do imaginário europeu acerca da natureza americana e seu impacto na obra de Marie. ************************************************************************************************************************************************************************************************************ The attraction of the unknown and the vision of America in the work of Marie van Langendonck Abstract: The book Uma Colônia no Brasil that is almost unknown in the academy. It was written by a belgium, Madame van Langendonck and has the purpose of describing her experiences in the Brazilian lands in the period she lived in a colony located in the south of the country, in the years 1857 to 1859. At sixty, Marie van Langendonck boards in an emigrant ship seduced by the desire of living in a virgin forest in Brazil. As soon as we believe the traveler had assimilated the edenic vision of a virgin world relived in the Romantic period, we intend to discuss the construction of the European American imaginary about nature and its impact on the work of Marie van Langendonck. Keywords: A Colony in Brazil; Mme. van Langendonck; Travel literature.